Pattern of Skin Diseases among Rural Adult Patients Attending the Dermatology OPD at A Tertiary Care Hospital Bangladesh - Islam, Kamrul; Islam, Md Imranul; Jahan, Tarana; Yusuf, Md Abdullah; Chowdhury, Sayema Hussain; Zohora, Fatima Tuj (Bangladesh Journal of Medical Microbiology, 2025)
Background: Skin diseases are common health problem in developing countries however they are not usually perceived to be a significant health concern. Skin diseases and their complications have remarkable effects on patient’s quality of life. Objective: The purpose of the present study was to observe the pattern of skin diseases and assess the relation of socio- demographic factors among rural adult patients attending the dermatology OPD at a tertiary care hospital Bangladesh. Methodology: A cross-sectional observational study was carried out in the department of Dermatology & Venereology of Monno Medical College & Hospital in Manikganj, Bangladesh from January 2022 to December 2022 for period of one year. Patients who were attending the dermatology OPD for skin problem during this period were included in this study. Dermatological diagnosis was done by qualified dermatologists from the outpatient department. A thorough medical history, clinical feature and detailed cutaneous examination was performed on each patient and diagnosis were made on the basis of clinical findings and some relevant investigations. Result: A total number of 2162 patients were recruited after fulfilling the inclusion and exclusion criteria. Among them majority patients aged between 18 to 30 years which was 1186 (54.9%), female patients were predominant 1276 (59.0%). In this study majority patients were house wife which was 797 (36.86%) followed by student 607(28.08%). The most common Pattern of dermatological disease was Infections and Infestation 915 (42.32%) followed by Dermatitis and Eczema 420 (19.43%), Acne Vulgaris 285 (13.18%) and Psoriasis 206 (9.53%). Noninfectious dermatoses were more than infectious group 1247 (57.68%) and 915 (42.32%) respectively. Among dermatological infection and infestation the most common was dermatophytosis which were 451(49.30%) and the second highest group was Scabies 204 (22.30%). Among the infective conditions, fungal infections was the most common disorder which was 531(58.03%) followed by parasitic infestations, bacterial infections and viral infections which were 209 (22.84%), 104 (11.36%) and 71 (7.76%) respectively. Conclusion: The frequency of skin diseases are increasing day by day. The pattern of skin diseases serves as an indicator of community development and the quality of available healthcare. Bangladesh Journal of Medical Microbiology, January 2025;19 (1):54-59